Is the OJIP Test a Reliable Indicator of Winter Hardiness and Freezing Tolerance of Common Wheat and Triticale under Variable Winter Environments? - Marcin Rapacz; Monika Sasal; Hazem M Kalaji; Janusz Kościelniak (PLoS ONE, 2015)
OJIP analysis, which explores changes in photosystem II (PSII) photochemical performance, has been used as a measure of plant susceptibility to stress. However, in the case of freezing tolerance and winter hardiness, which are highly environmentally variable, the use of this method can give ambiguous results depending on the species as well as the sampling year and time. To clarify this issue, we performed chlorophyll fluorescence measurements over three subsequent winters (2010/11, 2011/12 and 2012/13) on 220 accessions of common winter wheat and 139 accessions of winter triticale. After freezing, leaves were collected from cold-acclimated plants in the laboratory and field-grown plants. Observations of field survival in seven locations across Poland and measurements of freezing tolerance of the studied plants were also recorded. Our results confirm that the OJIP test is a reliable indicator of winter hardiness and freezing tolerance of common wheat and triticale under unstable winter environments. Regardless of species, the testing conditions giving the most reliable results were identical, and the reliability of the test could be easily checked by analysis of some relationships between OJIP-test parameters. We also found that triticale is more winter hardy and freezing tolerant than wheat. In addition, the two species were characterized by different patterns of photosynthetic apparatus acclimation to cold.